Censura: uma análise semiótica no title card do desenho animado Hora de Aventura (Adventure Time) - GOMES, Wesley Rogério Vaz. (2023)
This work has as main objective to analyze the Title Card of the cartoon Time of Adventure, both the original image and the modified one, under the Semiotic perspective. For this, it was used the general theory of the signs based on the triad of the relation between the sign and its object, considering the three points of view: the iconic one; The index; And the symbolic, according to Peirce's (2010) theory and the methodology adopted by Santaella (2010) in order to identify which semiotic looks enable this imagery to function as a sign, as well as contribute to an interpretive field unknown to the target audience of this content.